A New Era for Biotech Patents? Empirical and Theoretical Considerations on the current Patent Dilemma (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
During the last two decades, the genomics revolution has contributed enormously to the development of novel research approaches in the field of biological sciences. We have seen the development of new biotechnological tools capable of modifying organisms in order to perform specific tasks designing and assembling novel biological components. All these scientific and biotechnological innovations present also a substantial challenge for the law and especially for intellectual property rights. In particular – as a consequence of relevant patent case law in the United States and Europe affecting precision medicine – the debate on the possible future of biotech patents gained increasing momentum. Considering this multifaceted scenario, the purpose of this article is to analyse the impact of various judicial decisions with respect to patents subject-matter eligibility and the prosecution of biotech-related patent applications.
Keywords: Gene patents; genetic engineering; biotechnology; patents; CoViD-19